Ergonomia e design de vestimentas ocupacionais no Brasil: foco em equipamentos de proteção individual no setor de petróleo e gás - Leite, Charles [UNESP] (2014)
The design and deployment of artifacts with incorporated ergonomic properties or atributes, such as protective clothing, from ergodesign principles can serve as a tool to increase productivity, reduce incidents and accidents and improving the quality of life of workers involved in activity. This thesis is based on the principles of Ergonomics and Design, with a view to contributing to the access and dissemination of variables concering a comfortable work clothing for professionals in the oil and gas Brazilian. Wearable interfaces developed without attention to usability requirements lead to poor performance, and a reduction in the quality of the interaction between the subjects and their clothing. Therefore, that, for conducting this research thesis was structured four phases: a literature review, which showed the fragility and low domestic production on the theme. Documentary analysis, which brought together the current legislation and Brazilian standards indentifying certain omission when presented the gaps in effective prevention of incidents and accidents in the workplace. A heuristic evaluation, pointing out weaknesses in the usability of the National System of Management Personal Protective Equipment - PPE and a consultation of stakeholders, when analysis the speech of the institutions and agents responsible for regulating the protective clothing, target of this investigation, and pointed out certain inconsistencies